Teachers' support with ad-hoc collaborative networks - Cortez, C.; Nussbaum, M.; López, X.; Rodríguez, P.; Santelices, R.; Rosas, R.; Marianov, V. (Journal of computer assisted learning, 2005)
Efforts to improve the educational process must focus on those most responsible for implementing it: the teachers. It is with them in mind that we propose a face‐to‐face computer‐supported collaborative learning system that uses wirelessly networked hand‐held computers to create an environment for helping students assimilate and transfer educational content. Two applications of this system are presented in this paper. The first involves the use of the system by students, transforming classroom dynamics and enabling collaboration and interaction between the students and the teacher. In the second application, the system is used to help teachers update their knowledge of subject content and exchange methodological strategies.